2020
DOI: 10.1177/0739456x20949644
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Vulnerability for Inclusive Community Resilience: Photovoice Evidence from the Philippines

Abstract: This study explores the integration of photovoice with Facebook to demonstrate diverse dimensions of vulnerability through the lens of twenty-six informal settlers in metropolitan Manila and Cebu City. Through this mixed-methods approach, the article adds to the growing literature on vulnerability as an intrinsic and dynamic outcome of unjust social structures in the context of community resilience. Findings demonstrate the richness of vulnerability through a participant-driven approach, enhancing planners’ un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Finally, an emerging area of focus is the use photovoice in disaster studies, particularly within the field of disaster management and climate change (Russo et al, 2021). For example, two recent studies have applied photovoice to engage the voices of rural and indigenous community members recovering from natural disasters in Ontario, Canada (Russo et al, 2021), and to investigate the role of social capital in disaster settings to support community resilience in the Philippines (Cai, 2017).…”
Section: The Method: Photovoicementioning
confidence: 99%
“…Finally, an emerging area of focus is the use photovoice in disaster studies, particularly within the field of disaster management and climate change (Russo et al, 2021). For example, two recent studies have applied photovoice to engage the voices of rural and indigenous community members recovering from natural disasters in Ontario, Canada (Russo et al, 2021), and to investigate the role of social capital in disaster settings to support community resilience in the Philippines (Cai, 2017).…”
Section: The Method: Photovoicementioning
confidence: 99%
“…To date, the use of Photovoice in hazards research has been relatively limited. It has been used in relation to research themes of disaster tourism [33]; risk reduction and preparedness [50]; risk perception [7]; hazard resilience [41,[51][52][53]; community resilience [41,52]; and vulnerability [54]. In risk reduction and preparedness, Crabtree and Braun's [50] Hawai'i based study found Photovoice to be an effective tool for developing hazards risk awareness and risk reduction by building capacity to engage in preparedness actions.…”
Section: Use Of Photovoice Use Across Disciplinesmentioning
confidence: 99%
“…To date, the use of Photovoice in hazards research has been relatively limited. It has been used in relation to research themes of disaster tourism [33]; risk reduction and preparedness [50]; risk perception [7]; hazard resilience [41,[51][52][53]; community resilience [41,52]; and vulnerability [54]. In risk reduction and preparedness, Crabtree and Braun's [50] Hawai'i based study found Photovoice to be an effective tool for developing hazards risk awareness and risk reduction by building capacity to engage in preparedness actions.…”
Section: Use Of Photovoice Use Across Disciplinesmentioning
confidence: 99%